"Not a university type": focus group study of social class, ethnic, and sex differences in school pupils' perceptions about medical school. - Greenhalgh, T; Seyan, K; Boynton, P (2004)
OBJECTIVE: To investigate what going to medical school means to academically able 14-16 year olds from different ethnic and socioeconomic backgrounds in order to understand the wide socioeconomic variation in applications to medical school. DESIGN: Focus group study. SETTING: Six London secondary schools. PARTICIPANTS: 68 academically able and scientifically oriented pupils aged 14-16 years from a wide range of social and ethnic backgrounds. MAIN OUTCOME MEASURES: Pupils' perceptions of medical school, motivation to apply, confidence in ability to stay the course, expectations of medicine as a career, and perceived sources of information and support. RESULTS: There were few differences by sex or ethnicity, but striking differences by socioeconomic status. Pupils from lower socioeconomic groups held stereotyped and superficial perceptions of doctors, saw medical school as culturally alien and geared towards "posh" students, and greatly underestimated their own chances of gaining a place and staying the course. They saw medicine as having extrinsic rewards (money) but requiring prohibitive personal sacrifices. Pupils from affluent backgrounds saw medicine as one of a menu of challenging career options with intrinsic rewards (fulfillment, achievement). All pupils had concerns about the costs of study, but only those from poor backgrounds saw costs as constraining their choices. CONCLUSIONS: Underachievement by able pupils from poor backgrounds may be more to do with identity, motivation, and the cultural framing of career choices than with low levels of factual knowledge. Policies to widen participation in medical education must go beyond a knowledge deficit model and address the complex social and cultural environment within which individual life choices are embedded.